1998
DOI: 10.1007/bf01280321
|View full text |Cite
|
Sign up to set email alerts
|

Hypergravity can reduce but not enhance the gravitropic response ofChara globularis protonemata

Abstract: The relationship between the position of the statoliths and the direction and rate of tip growth in negatively gravitropic protonemata of Chara globularis was studied with a centrifuge video microscope. Cells placed perpendicularly to the acceleration vector (stimulation angle 90 degrees) showed a gradual reduction of the gravitropic curvature with increasing accelerations from 1 g to 8 g despite complete sedimentation of all statoliths on the centrifugal cell flank. It is argued that the increased weight of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The postulate of a cosine component is, as such, not entirely novel (see Introduction), but is applied in this work for the first time over a large dynamic range which enabled us to estimate the threshold for the cosine response. Our results are in agreement with data that were obtained with horizontally centrifuged coleoptiles of Avena (Bremekamp ) and with protonemata of Chara globularis (Hodick & Sievers ). In both of these organisms a large increase of the terrestrial gravity vector negatively affected the bending.…”
Section: Discussionsupporting
confidence: 92%
“…The postulate of a cosine component is, as such, not entirely novel (see Introduction), but is applied in this work for the first time over a large dynamic range which enabled us to estimate the threshold for the cosine response. Our results are in agreement with data that were obtained with horizontally centrifuged coleoptiles of Avena (Bremekamp ) and with protonemata of Chara globularis (Hodick & Sievers ). In both of these organisms a large increase of the terrestrial gravity vector negatively affected the bending.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, hypergravitropism was enhanced by 30 g in the gravitropic mutants tested in this study, suggesting that the observed attenuation in wild type is unlikely to be a result of mechanical bending/damage during application of hypergravity. Gravitropism in Arabidopsis roots and hypocotyls was also inhibited by hypergravity of more than 10 g (Fitzelle and Kiss, ), and hypergravity‐induced inhibition of gravitropism has also been observed in other plant species (Hodick and Sievers, ). These phenomena may reflect receptor desensitization or adaptation.…”
Section: Discussionmentioning
confidence: 98%
“…The reaction consists either of a change of growth direction and/or velocity or in differentiation, all of which involve a functioning cytoskeleton. Such responses to environmental stimuli are gravitropism (moss protonemata, Schwuchow et al ., 1990; Walker & Sack, 1995; and references therein, algal rhizoids and protonemata, Sievers & Schnepf, 1981 and references therein, Braun & Sievers, 1994; Hodick, 1994; Leitz et al ., 1995; Braun, 1997; Hodick & Sievers, 1998: fungi, Monzer, 1996), phototropism (moss, Meske et al ., 1996: fern, Kadota & Wada, 1989, 1992: algal zygotes, Fowler & Quatrano, 1997 and references therein) and reaction to physical features, chemical gradients or electrical fields (review Sievers & Schnepf, 1981). In moss protonemata MTs are involved in the positioning of chloroplasts according to the light circumstances (review Schnepf, 1986; Abel et al ., 1989, and references therein).…”
Section: Regulation Of the Cytoskeletonmentioning
confidence: 99%